2020
DOI: 10.3892/mmr.2020.11775
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑338‑3p regulates age‑associated osteoporosis via targeting PCSK5

Abstract: Bone loss is a disease that is highly associated with aging. This deleterious health condition has become a public concern worldwide, and there is an urgent need to discover more novel therapeutic strategies for the development of age-associated osteoporosis. The present study aimed to explore the association between proprotein convertase subtilisin/kexin type 5 (PCSK5) and microRNA(miR)-338-3p in bone-formation and bone-loss processes. Western blotting assay and reverse transcription-quantitative PCR were emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…PRDX1 (peroxiredoxin 1) is a known modulator of reactive oxygen species that regulates oxidative stress and BMP signalling-driven osteogenesis [ 35 ]. OXSM (mitochondrial 3-oxoacyl-ACP synthase) reportedly targets miR338-3p [ 36 ], which has important functions in regulating bone homeostasis in OP [ 37 ]. The present study confirmed that these genes—SLC7A11, RAC1, PRDX1 and OXSM—encoding disulfidptosis activators exhibited higher expression levels in OP samples, thereby activating disulfidptosis processes in OP.…”
Section: Discussionmentioning
confidence: 99%
“…PRDX1 (peroxiredoxin 1) is a known modulator of reactive oxygen species that regulates oxidative stress and BMP signalling-driven osteogenesis [ 35 ]. OXSM (mitochondrial 3-oxoacyl-ACP synthase) reportedly targets miR338-3p [ 36 ], which has important functions in regulating bone homeostasis in OP [ 37 ]. The present study confirmed that these genes—SLC7A11, RAC1, PRDX1 and OXSM—encoding disulfidptosis activators exhibited higher expression levels in OP samples, thereby activating disulfidptosis processes in OP.…”
Section: Discussionmentioning
confidence: 99%
“…MiR‐338‐3p is a miRNA that is shown to be involved in the prevention of osteoporosis by targeting a variety of signal molecules and signaling pathways, such as proprotein convertase subtilisin/kexin type 5 (PCSK5), Runx2, Fgfr2, and RANKL (Liu et al, 2014; Tong et al, 2021; Zhang et al, 2016). A study has indicated that RSV reduces the expression of miR‐338‐3p in ovariectomized rats.…”
Section: Resveratrolmentioning
confidence: 99%
“…Several studies reveal the involvement of microRNAs (miR-181a, miR-434-3p, miR-431, miR-29, and miR-126) in the skeletal muscle aging process [10][11][12]. The group of miRNAs such as microRNA-19b-3p (Liu et al, 2022) [13], miRNA-365a-3p [14], miRNA-577 [15], and miRNA-338-3p [16] is involved in the age-related bone loss.…”
Section: Introductionmentioning
confidence: 99%